2018
DOI: 10.1038/s41375-018-0075-3
|View full text |Cite
|
Sign up to set email alerts
|

Compound CAR T-cells as a double-pronged approach for treating acute myeloid leukemia

Abstract: Acute myeloid leukemia (AML) bears heterogeneous cells that can consequently offset killing by single-CAR-based therapy, which results in disease relapse. Leukemic stem cells (LSCs) associated with CD123 expression comprise a rare population that also plays an important role in disease progression and relapse. Here, we report on the robust anti-tumor activity of a compound CAR (cCAR) T-cell possessing discrete scFv domains targeting two different AML antigens, CD123, and CD33, simultaneously. We determined tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
76
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(77 citation statements)
references
References 25 publications
1
76
0
Order By: Relevance
“…Latest multi-center BCMA-CAR trials results indicate a relatively safe profile (although cytokine release syndrome -CRS and transient neurotoxicity were observed) with an overall response rate over 90% [145,146]. Other antigens currently being targeted to treat hematological malignancies include CD20 for NHL, CD138 for MM [144], CD33 [147], CD123 for AML [148,149] and CD7 for certain leukemias and lymphomas [150]. Lately, using a very elegant approach to treat T-cell malignancies, Pule and colleagues isolated an antibody specific for the TCRβ1 constant region.…”
Section: Beyond Cd19: New Car-t Cells For Solid Tumors -In Search Of mentioning
confidence: 96%
See 1 more Smart Citation
“…Latest multi-center BCMA-CAR trials results indicate a relatively safe profile (although cytokine release syndrome -CRS and transient neurotoxicity were observed) with an overall response rate over 90% [145,146]. Other antigens currently being targeted to treat hematological malignancies include CD20 for NHL, CD138 for MM [144], CD33 [147], CD123 for AML [148,149] and CD7 for certain leukemias and lymphomas [150]. Lately, using a very elegant approach to treat T-cell malignancies, Pule and colleagues isolated an antibody specific for the TCRβ1 constant region.…”
Section: Beyond Cd19: New Car-t Cells For Solid Tumors -In Search Of mentioning
confidence: 96%
“…This system was extensively characterized in the context of CAR expression but also of conditional secretion of checkpoint inhibitors, bi-specific T-cell engagers and alternatively, immunosuppressive molecule such as IL10 or PDL1 [306]. As aforementioned, an "OR" gate is represented by bi-specific CAR or dual-CAR expressing T cells [97,148].…”
Section: Control Of Transgene Expression and T-cell Functionmentioning
confidence: 99%
“…Multiple groups have also evaluated the retroviral transfer of human CD20 into T cells as a novel suicide gene mechanism for adoptive T cell therapy. Their data supports that infusion of the anti-CD20 antibody, rituximab, an approved antibody for in vivo therapeutic applications, results in efficient, specific elimination of CD20-positive T lymphocytes through ADCC [205,206,218]. Studies have also demonstrated that rituximab can eliminate CD20positive cells in vivo through inducing complementdependent cytotoxicity, a rapid and efficient mode of cell death [219].…”
Section: Suicide Genes and Safety Switchesmentioning
confidence: 64%
“…Several investigational CD33-targeted therapeutics have been developed for AML (26), including the recently FDA-approved anti-CD33 monoclonal antibody-drug conjugate gemtuzumab ozogamicin (GO, Mylotarg) (27), bispecific antibodies such as CD33/CD3 antibodies (28), CD33/CD123-directed CAR T cells (29). Although positive results have been reported from clinical trials of CD33-targeting drugs, dose limiting toxicities such as hepatotoxicities (30) during treatment are of concern.…”
Section: Discussionmentioning
confidence: 99%